2015
DOI: 10.1038/nrgastro.2015.98
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease and gluten-related disorders in childhood

Abstract: Gluten-related disorders such as coeliac disease, wheat allergy and noncoeliac gluten sensitivity are increasingly being diagnosed in children. Coeliac disease occurs frequently, affecting 1-3% of the Western population. The condition manifests at a very young age, more so in girls, and is related to the HLA genotype. Coeliac disease might be considered a public health problem and, as primary prevention is not possible, the debate on mass screening should be reopened. Wheat proteins, including gluten, are resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 124 publications
2
36
0
1
Order By: Relevance
“…The overall prevalence of celiac disease ranges from 4.5% among high-risk subjects to 0.75% in not-at-risk subjects[12]. High-risk subjects include the relatives of patients with celiac disease, children or adults with celiac disease-associated symptoms ( i.e ., diarrhea, abdominal pain and constipation) and children or adult subjects with celiac disease-associated disorders ( i.e ., Diabetes Mellitus type-1, Down syndrome, anemia, infertility, osteoporosis)[17]. It has been shown that celiac disease is not exclusive of industrialized countries, but includes North Africa, Middle East and India with an incidence overlapping those of European countries[18-20].…”
Section: Epidemiologymentioning
confidence: 99%
“…The overall prevalence of celiac disease ranges from 4.5% among high-risk subjects to 0.75% in not-at-risk subjects[12]. High-risk subjects include the relatives of patients with celiac disease, children or adults with celiac disease-associated symptoms ( i.e ., diarrhea, abdominal pain and constipation) and children or adult subjects with celiac disease-associated disorders ( i.e ., Diabetes Mellitus type-1, Down syndrome, anemia, infertility, osteoporosis)[17]. It has been shown that celiac disease is not exclusive of industrialized countries, but includes North Africa, Middle East and India with an incidence overlapping those of European countries[18-20].…”
Section: Epidemiologymentioning
confidence: 99%
“…Because the detergency of bile acids is obligatory for intestinal cholesterol uptake through micellar solubilization of the intraluminal sterols, the secretion of concentrated gallbladder bile to the small intestine greatly facilitates the digestion and absorption of dietary lipids. If impaired gallbladder contractility is restored by CCK‐1R agonists or bile acids such as cholic acid is fed, this may improve the symptoms of maldigestion and malabsorption such as diarrhoea, steatorrhoea, weight loss and nutritional deficiencies in coeliac patients . In addition, improving gallbladder kinetics may restore small intestinal motility and reduce contacting time of dietary gluten with the epithelial cells of the small intestine by accelerating its faecal excretion.…”
Section: Potential Role Of Cck‐1r Agonists In the Prevention Of Gallsmentioning
confidence: 99%
“…Although strict adherence to a gluten‐free diet (GFD) leads to prompt clinical and subsequent histologic improvement, clinical and histologic relapse often occurs when gluten is reintroduced . Celiac disease demonstrates a wide spectrum of clinical presentations with signs and symptoms of maldigestion and malabsorption such as diarrhea, steatorrhea, weight loss, and nutritional deficiencies . However, recent studies have increasingly characterized celiac patients as having symptoms less typical for classic malabsorption …”
Section: Introductionmentioning
confidence: 99%
“…3 Celiac disease demonstrates a wide spectrum of clinical presentations with signs and symptoms of maldigestion and malabsorption such as diarrhea, steatorrhea, weight loss, and nutritional deficiencies. [4][5][6][7] However, recent studies have increasingly characterized celiac patients as having symptoms less typical for classic malabsorption. 1,[8][9][10] The neuroendocrine peptide hormone cholecystokinin (CCK) is synthesized and secreted by the I-cells in the mucosal epithelium of the proximal small intestine.…”
Section: Introductionmentioning
confidence: 99%